Integrate, $$\int_{0}^{\frac{\pi}{2}}\sin (\tan\theta) \mathrm{d\theta}$$


2 Answers 2


First, make the change of variables $ x = \arctan(t) $ to transform the integral t0

$$\int_{0}^{\frac{\pi}{2}}\sin (\tan\theta) \mathrm{d\theta} = \int_{0}^{\infty}\frac{\sin(t)}{t^2+1} {dt} \\ = -\frac{1}{2}\,{{\rm e}^{-1}}{ \operatorname {E_1} } \left( -1 \right) +\frac{1}{2}\,{{\rm e}}\,{\operatorname{E_1}} \left( 1 \right) - \frac{1}{2}\,i\pi \,{{\rm e}^{-1}}$$

where $\operatorname{E}_a(z)$ is the exponential integral

$$ \operatorname{E}_a \left( z \right) =\int _{1}^{\infty }\!{{\rm e}^{-{t}z}}{{ t}}^{-a }{d{ t}}.$$

To see the details of evaluation of the last integral see here.

  • 2
    $\begingroup$ Good link and nice answer +1 $\endgroup$
    – Mikasa
    Dec 26, 2012 at 4:02
  • $\begingroup$ @BabakSorouh: Thank you for your comment. I really appreciate it. $\endgroup$ Dec 26, 2012 at 4:03
  • 3
    $\begingroup$ @MhenniBenghorbal The conventional notation is $\mathrm{E}_a(z)$, rather than $\mathrm{Ei}(a,z)$, see the wiki page about the exponential integral. $\endgroup$
    – Sasha
    Dec 26, 2012 at 18:37

Making a change of variables $u=\tan(\theta)$: $$ \int_0^{\pi/2} \sin\left(\tan \theta\right) \mathrm{d} \theta = \int_0^\infty \frac{\sin(u)}{1+u^2} \mathrm{d} u \tag{1} $$ In order to evaluate this we use the technique of Mellin transform.

  1. Evaluate the Mellin transforms of $\sin(u)$ and $\left(1+u^2\right)^{-1}$: $$ \mathcal{M}_s(\sin(u))= \int_0^\infty u^{s-1} \sin(u) \mathrm{d} u = \frac{\sqrt{\pi}}{2} 2^{s} \frac{\Gamma\left(\frac{1}{2} + \frac{s}{2}\right)}{\Gamma\left(1-\frac{s}{2}\right)} $$ defined in the strip $-1<\Re(s)<1$. Applying the inverse transform: $$ \sin(u) = \frac{1}{2 \pi i} \int_{\gamma - i \infty}^{\gamma + i \infty} \frac{\sqrt{\pi}}{2} 2^{s} \frac{\Gamma\left(\frac{1}{2} + \frac{s}{2}\right)}{\Gamma\left(1-\frac{s}{2}\right)} u^{-s} \mathrm{d} s \tag{2} $$ where $\gamma$ is an arbitrary real constant such that $-1<\gamma<1$. The Mellin transform of the rational function $(1+u^2)^{-1}$ reads $$ \mathcal{M}_s\left(\frac{1}{1+u^2}\right)= \int_0^\infty \frac{u^{s-1}}{1+u^2}\mathrm{d} u = \frac{1}{2} \Gamma\left(\frac{s}{2}\right) \Gamma\left(1-\frac{s}{2}\right) \tag{3} $$ and is defined in the strip $0<\Re(s)<2$.

  2. Now substituting $(2)$ into $(1)$, choosing $\gamma$ such that $-1<\gamma<0$, and interchanging the order of integration: $$\begin{eqnarray} \int_0^\infty \frac{\sin(u)}{1+u^2} \mathrm{d} u &=& \frac{1}{2\pi i} \frac{\sqrt{\pi}}{2} \int_{\gamma-i \infty}^{\gamma+i \infty} 2^{s} \frac{\Gamma\left(\frac{1}{2} + \frac{s}{2}\right)}{\Gamma\left(1-\frac{s}{2}\right)} \left( \int_0^\infty \frac{u^{-s}}{1+u^2} \mathrm{d}u \right) \mathrm{d} s \\ &\stackrel{(2)}{=}& \frac{1}{2\pi i} \frac{\sqrt{\pi}}{2} \int_{\gamma-i \infty}^{\gamma+i \infty} 2^{s} \frac{\Gamma\left(\frac{1}{2} + \frac{s}{2}\right)}{\Gamma\left(1-\frac{s}{2}\right)} \left(\frac{1}{2} \Gamma\left(\frac{1-s}{2}\right) \Gamma\left(1-\frac{1-s}{2}\right) \right)\mathrm{d} s \\ &=& \frac{1}{2\pi i} \frac{\sqrt{\pi}}{4} \int_{\gamma-i \infty}^{\gamma+i \infty} \Gamma\left(\frac{1}{2}-\frac{s}{2}\right) \frac{\Gamma\left(\frac{1}{2}+\frac{s}{2}\right)^2}{\Gamma\left(1-\frac{s}{2}\right)} \left(\frac{1}{2}\right)^{-s} \mathrm{d}s \\ &\stackrel{\text{reflection}}{=}& \frac{1}{2\pi i} \frac{\pi}{2} \int_{\gamma - i \infty}^{\gamma+i \infty} \Gamma(s) \tan\left(\frac{\pi}{2} s \right) \mathrm{d}s \end{eqnarray} $$ The latter integral can be evaluated as a sum over residues at poles to the left of the integration contour, situated at odd negative integers. The poles of $\Gamma(s)$ are even non-positive integers are canceled by zeros of the tangent function. The poles at the odd negative integers are double poles: $$ \operatorname{Res}_{s=-2k-1} \left(\frac{\pi}{2} \Gamma\left(s\right) \tan\left(\frac{\pi}{2} s\right) \right) = \frac{1}{\Gamma\left(2k+2\right)} \psi\left(2k+2\right) $$ where $\psi(x)$ is the digamma function.

Thus we have the result: $$\begin{eqnarray} \int_0^\infty \frac{\sin u}{1+u^2} \mathrm{d} u &=& \sum_{k=0}^\infty \frac{\psi(2k+2)}{\Gamma(2k+2)} = \frac{1}{2} \left( \sum_{k=0}^\infty \frac{\psi(k+1)}{\Gamma(k+1)} - \sum_{k=0}^\infty (-1)^k \frac{\psi(k+1)}{\Gamma(k+1)}\right) \\ &=& \frac{1}{2} \left(f(1) - f(-1)\right) = \frac{\exp(-1)}{2} \operatorname{Ei}(1) - \frac{\exp(1)}{2} \operatorname{Ei}(-1) \end{eqnarray} $$ where $\operatorname{Ei}(x)$ denotes the exponential integral special function. We now proceed to prove that, for real non-zero $x$: $$ f(x) = \sum_{k=0}^\infty x^k \frac{\gamma(k+1)}{\Gamma(k+1)} = \mathrm{e}^{x} \left( \frac{1}{2} \log(x^2) - \operatorname{Ei}(-x) \right)$$ Indeed, denoting the Euler-Mascheroni constant as $C$, and using $H_n = -\sum_{k=1}^n \frac{(-1)^k}{k} \binom{n}{k}$: $$\begin{eqnarray} \sum_{k=0}^\infty x^k \frac{\gamma(k+1)}{\Gamma(k+1)} &=& \sum_{k=0}^\infty x^k \frac{-C +H_{k}}{k!} = - C \mathrm{e}^{x} - \sum_{k=1}^\infty \frac{x^k}{k!} \sum_{m=1}^k \frac{(-1)^m}{m} \binom{k}{m} \\ &=& -C \mathrm{e}^{x} - \sum_{m=0}^\infty \frac{x^m}{m!} \sum_{k=1}^\infty \frac{(-x)^k}{k \cdot k!} = -C \mathrm{e}^{x} - \mathrm{e}^{x} \left( \operatorname{Ei}(-x) - \log |x| -C \right) \\ &=& \mathrm{e}^{x} \left( \log |x| - \operatorname{Ei}(-x) \right) \end{eqnarray}$$

  • $\begingroup$ +1 Involved, but cool nonetheless. $\endgroup$
    – user40314
    Dec 26, 2012 at 18:53

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.